Efficient nitrogen fertilization for sustainable sago palm (Metroxylon sagu Rottb.) cultivation in Tropical Peatland - Yuka Sasaki; Ho Ando; Ken-Ichi Kakuda; Lulie Melling; Akira Watanabe (Plant Production Science)
Tropical peatlands degraded by agricultural use with intensive drainage require restoration through rewetting, preferably while agricultural use continues. Sago palm (Metroxylon sagu Rottb.), a starch crop that can grow in high water table peatlands, is suitable for this objective. However, the optimal method of sago palm cultivation on peat soil has not yet been established. To establish an efficient nitrogen (N) fertilization method for sustainable production of sago palm in peatland, the fate of 15N-labelled urea applied to sago palm after transplanting and the effect of controlled-release N fertilizer applied before transplanting on sago palm growth were examined in field experiments in Malaysia. The rate of mineralization of soil organic N was also measured to evaluate the capacity of soil N as another N source for sago palms. The application of chemical fertilizers after transplanting did not improve plant growth or total N uptake. After 1 year, only 2–5% and 9–22% of the fertilized N was detected in aboveground parts (mother plant and suckers) and soil, respectively. The N supplying potential of peat soils exceeded the N requirements of sago palms. In contrast, N application at the nursery stage increased leaf length, number of leaves, aboveground biomass, and leaf chlorophyll content after transplanting. These results suggest that concentrating fertilization at the nursery stage would be an efficient method for sago palm cultivation in tropical peatlands.